STRATEGI DIGITAL STORYTELLING PADA ORGANISASI CROWDFUNDING DI MEDIA SOSIAL INSTAGRAM @LAZISNUBANYUWANGI - Assilah, Qonita Imania (IAI Darussalam, 2023)
This study aims to identify and explain a digital storytelling strategy by LAZISNU Banyuwangi as a crowdfunding organization. The results of this study show that LAZISNU Banyuwangi uses a digital storytelling strategy to carry out crowdfunding activities by creating narratives that can persuade the audience to build an emotional side and evoke compassion in the audience so they want to help by donating. The narrative strategy used by LAZISNU Banyuwangi has guidelines that are in accordance with Clandinin & Polkinghorne which consist of settings, characters, and plots.